2007
DOI: 10.1177/0003319707306146
|View full text |Cite
|
Sign up to set email alerts
|

Association of Drinking Pattern and Alcohol Beverage Type With the Prevalence of Metabolic Syndrome, Diabetes, Coronary Heart Disease, Stroke, and Peripheral Arterial Disease in a Mediterranean Cohort

Abstract: The purpose of this study was to investigate the relationship between alcohol consumption and the prevalence of the metabolic syndrome (MetS), type 2 diabetes mellitus (DM), coronary heart disease (CHD), stroke, peripheral arterial disease (PAD), and overall cardiovascular disease (CVD) in a Mediterranean cohort. It consisted of a cross-sectional analysis of a representative sample of Greek adults (n = 4,153) classified as never, occasional, mild, moderate, or heavy drinkers. Cases with overt CHD, stroke, or P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
83
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 48 publications
(42 reference statements)
5
83
1
6
Order By: Relevance
“…Durante el seguimiento (mediana [intervalo intercuartílico], 4,2 [2,[5][6],1] años) se identificaron 554 casos incidentes de hipertensión entre 43.562 personasaño. La hazard ratio (HR) de hipertensión para un consumo de alcohol ≥ 5 días por semana fue 1,28 (intervalo de confianza [IC] del 95%, 0,97-1,70) comparados con abstemios.…”
unclassified
See 1 more Smart Citation
“…Durante el seguimiento (mediana [intervalo intercuartílico], 4,2 [2,[5][6],1] años) se identificaron 554 casos incidentes de hipertensión entre 43.562 personasaño. La hazard ratio (HR) de hipertensión para un consumo de alcohol ≥ 5 días por semana fue 1,28 (intervalo de confianza [IC] del 95%, 0,97-1,70) comparados con abstemios.…”
unclassified
“…During follow-up (median [interquartile range], 4.2 [2. [5][6].1] years), 554 incident cases of hypertension were identified over a total of 43,562 person-years. The hazard ratio for hypertension among those who consumed alcohol on ≥5 days per week was 1.28 (95% confidence interval, 0.97-1.7) compared to abstainers.…”
mentioning
confidence: 99%
“…Results from Greek adult population study showed that moderate alcohol consumption was associated with a lower prevalence of MS compared with no alcohol use in a Mediterranean cohort [30]. Also wine consumption was associated with a slightly higher effect than beer or spirits consumption on the prevalence of total cardiovascular disease, and beer consumption [29][30][31]. The results of a crosssectional study, which was conducted among high cardiovascular risk participants of the Reus PREDIMED Centre, showed that red wine, as one component of the Mediterranean diet, was associated with lower prevalence of MS [31].…”
Section: Data Adjusted For Age Education and All Listed Lifestyle Famentioning
confidence: 97%
“…The results from Family Heart Study showed that alcohol consumption was associated with a lower prevalence of MS irrespective of the type of beverage consumed [28]. Results from Greek adult population study showed that moderate alcohol consumption was associated with a lower prevalence of MS compared with no alcohol use in a Mediterranean cohort [30]. Also wine consumption was associated with a slightly higher effect than beer or spirits consumption on the prevalence of total cardiovascular disease, and beer consumption [29][30][31].…”
Section: Data Adjusted For Age Education and All Listed Lifestyle Famentioning
confidence: 97%
See 1 more Smart Citation